Mixed convection boundary-layer flow from a horizontal circular cylinder with a constant surface heat flux - Nazar, Roslinda; Amin, Norsarahaida; Pop, Ioan (Springer Berlin / Heidelberg, 2004)
The laminar mixed convection boundary-layer flow of a viscous and incompressible fluid past a horizontal circular cylinder, which is maintained at a constant heat flux and is placed in a stream flowing vertically upward has been theoretically studied in this paper. The solutions for the flow and heat transfer characteristics are evaluated numerically for different values of the mixed convection parameter k with the Prandtl number Pr = 1 and 7, respectively. It is found, as for the case of a heated or cooled cylinder, considered by Merkin [5], that assisting flow delays separation of the boundary-layer and can, if the assisting flow is strong enough, suppress it completely. The opposing flow, on the other side, brings the separation point nearer to the lower stagnation point and for sufficiently strong opposing flows there will not be a boundary-layer on the cylinder